Reimagining education for transformation and social change: A case study of integrated learning at UCBC in the DRC - Bunduki, K.H.; Higgs, L.G. (South African Journal of Higher Education, 2017)
This article examines the case of integrated learning at the Christian Bilingual University of the Congo (UCBC) in the Democratic Republic of the Congo. A description of the integrated learning as an igniter of transformation in learners was obtained through the analysis of data collected from twelve alumni through semi-structured interviews. An explanation of how learners are impacted through integrated learning to serve as change agents in their communities also emerged from the data analysis. In fact, the curriculum at UCBC was described as having multiple components and dimensions. This curriculum equips learners with academic knowledge and skills, and it fosters character and servant leadership skills in them. The major components of the curriculum are the academic training, the special skills training, the work program, service-learning and community life, and its dimensions are affective, social and relational. Learning occurs in a family-like environment characterized by accessibility and free interactions between members of the campus community. The curriculum functions under an overall Christian worldview. As a result of the educational process they underwent students became role models and learning-teachers to their colleagues and community members. Key terms: Christian university, curriculum, integrated learning, servant leadership, transformation, triadic training